26 Gabapentin and pregabalin use, misuse and associated risks in the palliative care setting. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Doherty, M; McQuillan, R
Abstract : Background: Gabapentin and pregabalin are antiepileptic medications licensed for the treatment of neuropathic pain. The Department of Health has highlighted the need for vigilance when prescribing these medications due to their misuse and associated risks: dependency, CNS depression, seizure activity and mortality. Furthermore, due to the frequency of withdrawal symptoms, the manufacturers have recommended that pregabalin should be weaned gradually over a minimum of one week. Objectives: To; Assess prescribing practices, frequency of misuse and frequency of serious adverse events in relation to gabapentin/pregabalin in the palliative care setting Methods An anonymous survey was designed and administered using SurveyMonkey. It was distributed via email link to palliative medicine physicians (PMPs) and palliative care nurse specialists (PCNSs) Results: 49 responses were received- 36 from PMPs, 13 from PCNSs. 48/49 respondents prescribe or advise gabapentin/pregabalin. 94% of respondents prescribe pregabalin more frequently than gabapentin. When discontinuing gabapentin/pregabalin, 16% stop without weaning, 6% wean over three days, 20% wean over one week, 56% wean over one week or more. Seizure activity and respiratory depression secondary to gabapentin/pregabalin was reported by 6% (3/49) of respondents. 8% (4/49) of respondents reported that they suspected or believed some of their patients to have misused gabapentin/pregabalin- none reported their concerns to the UK Committee on the Safety of Medicines or the Health Products Regulatory Authority. Conclusions: Gabapentin and pregabalin are commonly prescribed in palliative care, practices vary with regard to weaning the medications, and serious adverse events and misuse of these medications are occurring but are not being reported. Respondents displayed a growing awareness of the abuse potential of these medications in the comments section of the survey and report having modified their prescribing practices on account of this.